2017
DOI: 10.1037/neu0000323
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal emotion processing deficits are present in amyotrophic lateral sclerosis.

Abstract: These results indicate that people living with ALS without dementia often have subtle difficulties with recognizing emotions in both faces and voices, even in the context of intact basic cognition. Clinicians should be aware of the potential for these emotion processing difficulties to be present in ALS and to affect interpersonal behavior and quality of life. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Even though it is well established that ALS patients have impairments in emotion recognition 1 , some studies in the field did not control for FTD-related behavioral symptoms 6,9,13 . Interestingly, after categorizing ALS patients into those with (ALSbs) or without (ALSns) frontal features, only the subgroup with coexisting behavioral impairment (ALSbs) was impaired in emotion recognition, as previously reported 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it is well established that ALS patients have impairments in emotion recognition 1 , some studies in the field did not control for FTD-related behavioral symptoms 6,9,13 . Interestingly, after categorizing ALS patients into those with (ALSbs) or without (ALSns) frontal features, only the subgroup with coexisting behavioral impairment (ALSbs) was impaired in emotion recognition, as previously reported 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether emotion recognition deficits in ALS occur in the absence of behavioral changes, as some of the previous studies in the field did not assess frontal behavioral symptoms with specific tools 6,9,13 . It remains open the issue whether emotion recognition deficits can occur independently of frontal behavioral syndrome in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Meta analyses report moderate deficits in facial emotion recognition for anger, sadness and disgust ( 132 ) and for disgust and surprise, respectively ( 67 )–an inconsistency that can probably be explained amongst others reasons by the heterogeneity of the used measures and of the clinical and cognitive features of the mainly small study samples. A recent study confirmed deficits of correct emotion recognition in face as well as in voice even for ALS-patients with otherwise unimpaired cognitive abilities, but particularly for complex emotion expressions ( 133 ). Irrespective of the specific (negative) emotions though, a lacking ability of identifying and consequently attributing them correctly and responding to them adequately can be considered to be very dissatisfying for patient and interlocutor, causing frustration and interpersonal conflicts; all aspects possibly affecting HT-AAC use and validity of QoL measures of locked-in patients which has not yet been studied.…”
Section: Cognitive and Behavioral Impairment And Its Consequences Formentioning
confidence: 75%
“…Despite cognitive deficits–although not independent from them and often hard to distinguish ( 108 )–frontal lobe dysfunction is associated with various significant behavioral changes and neuropsychiatric symptoms in ALS, frequently disinhibition, mood disturbances, and in particular apathy ( 104 , 108 , 133 , 139 , 143 147 ). Regarding the issue of patient's motivation to communicate, studies by Lillo et al ( 124 , 143 ) for example found significant symptoms of apathy in ALS, particularly a crucially limited motivation in 80% and a significant apathy in about 40% of the 92 enrolled patients ( 143 ).…”
Section: Cognitive and Behavioral Impairment And Its Consequences Formentioning
confidence: 99%
See 1 more Smart Citation